The advocate ophiolite mantle, Baie Verte, Newfoundland: Regional correlations and evidence for metasomatism - Bédard, Jean H. (2010)
Mantle rocks of the Advocate ophiolite near Flatwater Pond (Baie Verte, Newfoundland) are dominated by harzburgite tectonites, which are extensively converted to listvenite along the Baie Verte Road fault and represent a potential gold exploration target. Most Advocate harzburgites have forsteritic olivine (Fo90.5 to Fo93) and Cr-spinels, with Cr# (= 100Cr/(Cr + Al)) between 52 and 64 and Mg# (= 100Mg/(Mg + Fe2+)) between 56 and 68. These mineral chemical signatures, together with high whole-rock MgO (46%-48%), low Al2O3 (<1%), and TiO2 (<0.003%), imply the Advocate harzburgites are refractory residues after ca. 25%-35% melting. Cr-spinel compositions of Advocate mantle rocks overlap with Cr-spinels from the mantle rocks of the Point Rousse and Betts Cove ophiolites, with Mg# higher than those of Bay of Islands or Thetford Mines mantle Cr-spinels. Although refractory in terms of major elements and mineral chemistry, Advocate harzburgites contain high La-Ce-Pr-Pb-Nd-Sm-Zr contents suggestive of pervasive metasomatism. Similar geochemical signatures occur in all ophiolitic mantle rocks from the Baie Verte Peninsula examined so far. The enrichments are not consistent with supra-subduction zone syn-melting metasomatism as observed in other Appalachian ophiolites. The apparent absence of visible metasomatic channels in most outcrops suggests that metasomatism occurred before obduction by diffuse percolation, but the nature and origin of the metasomatic agent remain speculative. The similarities of mineral and whole-rock geochemistry imply that all mantle rocks from Baie Verte ophiolites are correlative and may represent remnants of a single obducted slab.